How chronotype, sleep-wake cycle, subjective time experience influence retrospective, and prospective memory functioning - Fabbri, Marco; Martoni, Monica (Frontiers in Cognition, 2025)
BackgroundThe sleep-wake cycle and chronotype are key contributors to memory consolidation. Emerging evidence also highlights their role in shaping the subjective experience of time, which, in turn, can influence cognitive performance, particularly memory. This study investigated how sleep-wake quality, circadian typology, and subjective time perception relate to failures in retrospective and prospective memory.MethodA total of 666 participants (73% female; M = 37.83 years, SD = 14.65) completed the reduced Morningness-Eveningness Questionnaire (rMEQ), Mini-Sleep Questionnaire (MSQ), Prospective and Retrospective Memory Questionnaire (PRMQ), Subjective Time Questionnaire (STQ), and ad hoc questions about sleep habits during weekdays and weekends.ResultsResults indicated that evening-types reported later sleep and wake times, more pronounced sleep-wake disturbances, greater memory lapses, and stronger experiences of time expansion/boredom. Correlational analyses showed that both time pressure and time expansion/boredom were negatively associated with PRMQ scores, leading to increased memory errors. The regression models showed that memory performance was generally predicted by wake factor, time pressure and time expansion/boredom. Then, mediation models revealed that eveningness was associated with greater wake problems, which were positively related to altered time perception (i.e., time pressure and time expansion/boredom), which in turn predicted more frequent retrospective and prospective memory failures.DiscussionThese findings suggest that circadian typology, wake-related disturbances, and subjective time perception interactively contribute to memory performance, and propose a model linking biological rhythms and temporal experience to memory functioning, suggesting a possible influence of attention and arousal.